A Structural Equation Model for Consumers’ Mobile-based Information Search: A Case of Outbound Chinese Tourists - Chaang-Iuan Ho; Ming-Chih Chen; Yu-Lan Yuan (International Journal of Supply Chain Management, 2017)
This research responds to the call for more studies to validate a comprehensive model incorporating mobile Internet and other information channels to investigate their effects within the search process. Using 104 Chinese outbound tourists as the sample, this study investigates how they utilize multiple sources for trip planning. The research findings indicate that mobile-based search actions have been undertaken step by step: internal search mobile search preliminary collaborative TIS saving information summarizing information. Two search patterns were identified by using other information sources: 1. mobile Internet advanced collaborative TIS editorial communications; 2. mobile Internet PC Internet editorial communications. In spite of the studys limitations in relation to generalizing the results, this study presents new avenues for further research.